Hilangnya Karakter Religius Siswa Pasca Pandemi: Upaya Model Keteladanan Guru Madrasah Ibtidaiyah - Setiowati, Julia; Faliyandra, Faisal (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Post-covid-19 reaped many problems in the world of education, one of which was the decline in the religious character of students. Indonesia's own religious character needs to be considered by academics, seeing God as the main basis of the nation which is implemented in education, especially in Madrasas. So the purpose of this research is to see the efforts of teachers to apply exemplary models to improve religious character in Madrasah Ibtidaiyah. The Classroom Action Research (PTK) approach was used to elicit problems that occurred in this study with class-based subjects. The subjects of this study were 12 grade VI students at Miftahul Huda Islamic Elementary School (MI). The results of the study state that the exemplary model is one of the models that can be used by teachers in improving the character of students. It is hoped that in the future this method will become a practical choice that can be used by teachers in the classroom. The explanation of the results in detail will be presented in this study.